2010
DOI: 10.1016/j.freeradbiomed.2010.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Plasma nitrite flux predicts exercise performance in peripheral arterial disease after 3months of exercise training

Abstract: Plasma nitrite is a major oxidation product of nitric oxide. It has also recently been suggested to perform an endocrine-like function as a nitric oxide donor in hypoxic tissues, allowing vasodilation. Exercise performance is limited in peripheral arterial disease due to an inadequate blood supply to working tissues. We hypothesized that exercise training in peripheral arterial disease subjects will demonstrate improved "plasma nitrite flux" and endothelial function, to accompany increased exercise performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
62
0
9

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 39 publications
10
62
0
9
Order By: Relevance
“…11 Nitrite stores decrease following exercise among individuals with PAD, with and without diabetes (40% reduction), compared with healthy individuals. 12,13 These results are consistent with use of NO stores in an attempt to normalize blood flow and oxygen delivery. As nitrite stores become depleted, the resulting loss of NO may contribute to abnormal endothelial function and circulatory responses in PAD.…”
Section: Introductionsupporting
confidence: 72%
“…11 Nitrite stores decrease following exercise among individuals with PAD, with and without diabetes (40% reduction), compared with healthy individuals. 12,13 These results are consistent with use of NO stores in an attempt to normalize blood flow and oxygen delivery. As nitrite stores become depleted, the resulting loss of NO may contribute to abnormal endothelial function and circulatory responses in PAD.…”
Section: Introductionsupporting
confidence: 72%
“…23 Failure to control for the impact of diet on NO levels is not only a limitation of our study but also of previous studies which in contrast to us, have demonstrated improvement in NO bioavailability following SET in claudicants. 24 A variation in dietary intake may therefore provide some explanation for such contrasting results. Furthermore, Allen et al 24 measured nitrite levels only which are rapidly metabolised to nitrate and therefore unlikely to provide an accurate representation of total endogenous NO production.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that NO availability declines with age [11,12] and can be further compromised by the presence of atherosclerotic disease, as observed in PAD [13]. However, the cause for low NO availability in PAD is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In PAD, there is evidence that NO availability is closely associated with exercise tolerance [13]. We assessed the relationship between leg blood flow and amounts of the enzymes that produce NO and ROS, as ROS production directly impacts NO bioavailability [17].…”
mentioning
confidence: 99%